The Past as a Multi-perspective Structure in Matthew Kneale’s English Passengers - Kucała, Bożena (American & British Studies Annual, 2020)
Matthew Kneale’s neo-Victorian novel English Passengers (2000) is underlain by contemporary, revisionist views of Victorian ideologies. In particular, by placing its action on board a ship headed towards Tasmania as well as in Tasmania itself, the novel examines colonial attitudes and relations between cultures. Accordingly, it has been analysed as a novel about national identity and imperial politics (Boccardi 2009). This article takes the novel’s form as the starting point for analysis. Told in twenty voices, with events developing on two temporal planes which continually intersect and eventually converge, English Passengers foregrounds the co-existence of multiple perspectives and the simultaneity of events in its representation of the past, and by doing so it disrupts the convention of narrative. The article argues that, rather than relying on linearity and causality, Kneale’s novel constructs an image of the past as a structure with many dimensions, in which temporal change depends on a variety of overlapping, conflicting or convergent points of view and attitudes. Ultimately, the discussion attempts to demonstrate that through its structure English Passengers, without being overtly metafictional or metahistorical, addresses the problem of representing the past.